2007
DOI: 10.1007/s00774-007-0753-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bone resorption genes in osteoarthritis and in osteoporosis

Abstract: Cathepsin K and MMP-9 are considered to be the most abundant proteases in osteoclasts. TRAP is a marker for osteoclasts, and there is increasing evidence of its proteolytic role in bone resorption. RANKL is a recently discovered regulator of osteoclast maturation and activity and induces expression of many genes. This study compared cathepsin K, MMP-9, TRAP, RANKL, OPG, and osteocalcin gene expression in the proximal femur of patients with osteoarthritis with that of patients with femoral neck fracture. Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 34 publications
10
89
1
Order By: Relevance
“…MMP activity is normally inhibited by TIMPs (tissue inhibitor of metalloproteinases), but research suggests that that these inhibitors themselves are down-regulated at senescence, thereby further contributing to matrix degradation (Hornebeck 2003). MMP secretion by senescent cells has been suggested to play a role in the progression of disease such as in the pathogenesis of coronary heart disease (CAD) (Nanni et al 2007), and implicated in the progression of osteoporosis, since MMPs play important roles in bone resorption (Logar et al 2007). Price et al (2002) has also shown that the secretion of MMPs by senescent chondrocytes may contribute to the development or progression of osteoarthritis.…”
Section: Biological Impact Of the Senescent Phenotypementioning
confidence: 99%
“…MMP activity is normally inhibited by TIMPs (tissue inhibitor of metalloproteinases), but research suggests that that these inhibitors themselves are down-regulated at senescence, thereby further contributing to matrix degradation (Hornebeck 2003). MMP secretion by senescent cells has been suggested to play a role in the progression of disease such as in the pathogenesis of coronary heart disease (CAD) (Nanni et al 2007), and implicated in the progression of osteoporosis, since MMPs play important roles in bone resorption (Logar et al 2007). Price et al (2002) has also shown that the secretion of MMPs by senescent chondrocytes may contribute to the development or progression of osteoarthritis.…”
Section: Biological Impact Of the Senescent Phenotypementioning
confidence: 99%
“…Osteocalcin gene and protein expression is increased in OA bone indicating higher bone resorption and bone formation in OA compared to the healthy situation. 32,33 Therefore, when comparing with bone samples from healthy subjects, an unambiguous increase in osteocalcin deposition in ONFH bone matrix might be detectable. We detected an increased bone volume and bone volume fraction in the femoral canal when assessing trabecular microarchitecture.…”
Section: Growth Factors and Bone Quality In Femoral Metaphysis In Onfhmentioning
confidence: 99%
“…MMPs play a crucial role in tissue remodeling and in the destruction of bone in an arthritic joint due to their ability to degrade a wide variety of extracellular matrix components (26). In particular, MMP-9 is essential with respect to the initiation of the osteoclastic resorption process via removal of the collagenous layer from the bone surface prior to demineralization (27,28). Moreover, MMP-9-knockout mice display only transient disturbances in bone development (27,29).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MMP-9 is essential with respect to the initiation of the osteoclastic resorption process via removal of the collagenous layer from the bone surface prior to demineralization (27,28). Moreover, MMP-9-knockout mice display only transient disturbances in bone development (27,29). An in vitro experiment involving calvarial bone revealed that digestion of the bone matrix is inhibited in the presence of an MMP inhibitor (27,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation